MEENA KANDASAMY AS FEMALE WRITER OF DALIT LITERATURE - Sanghamitra Goswami; Dr. Anushruti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A country that is steeped in a wide variety of traditional institutions that present a challenge for the nation, India is a country that is rich in diversity. Certain strict rules do not allow time to regulate itself, despite the fact that all societies that have time are open to transitions. All societies, religions, regions, and social classes are constantly striving to emerge, but they fail to recognize the same need for women and girls. That being said, undoubtedly, this class is a component of India's disenfranchised population. Indian women have always been subjected to the oppressions of society in a variety of different ways. Caste, creed, and gender have all contributed to the further division of the community. The article seeks to show the pitiful position of Dalit women in free India, with a particular focus on Meena Kandasamy's literary excellence in The Touch and Ms. Militancy. This attempt is made in light of the fact that India has recently become a free nation. In dalit society, she has done a good job of acting as a spokesperson for her sexual orientation. In her efforts to bring about positive improvements in the lives of members of society's underprivileged class, she has spared no effort in her pursuit of this goal. This so-called civilized nation is in for a rude awakening as a result of her representation of the lower strata. It is only in the "dreams of our India" that Meena is able to conjure up the possibility of a miraculous shift taking place within the nation. She talks about the predicament that the women are in and the conditions that led to the unfair treatment that they received. In an effort to improve the lives of dalit people, Meena makes use of her literary brilliance to investigate the more negative aspects of society. Attempting to gain a deeper understanding of the universal miseries experienced by the underprivileged group, this paper is an attempt to explore the writings of dalit female writers.